Experiences with the shikimate-pathway enzymes as targets for rational drug design. (1st June 2003) - Coggins, J.R.; Abell, C.; Evans, L.B.; Frederickson, M.; Robinson, D.A.; Roszak, A.W.; Lapthorn, A.P.
Abstract : The background and current context of work on the shikimate-pathway enzymes as potential targets for anti-bacterial, anti-fungal and anti-parasitic drugs is reviewed. Recent work on the third enzyme of the pathway, dehydroquinase, which occurs in two structurally and mechanistically distinct forms, is used to illustrate the present state of studies into rational drug design.